Memories of old Manila [videorecording] (NCCA, 1993)
An exploration of five centuries of Manila, and into the lives of street kids, addicts, transvestites and student activists who cross paths with imaginary figures of mermaids, giants and Oliver who represents Philippine underground cinema.